(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Desertification is a form of land degradation which is affecting many parts of the world. Climatic changes are considered as a major cause for the degradation of natural resources. Once the desertification is caused by natural or human causes it affects the productivity of the land. The spread of desert-like conditions is directly linked to the slow advancement of the desert towards the productive land by shifting dunes, winds, intense heating of land and also a scarcity of rainfall. Rainfall is an important phenomenon which is responsible for groundwater replenishment. In case of scarcity of rainfall, there will be a shortage of water which may cause drought in a region. Advancement of Thar towards the eastern side of Rajasthan is a big issue. Efforts are being made to identify the areas prone to desertification and restore the ecology before the condition becomes irreversible. According to a report published by ISRO in Desert Atlas of India, effects of desertification are now visible in Ajmer and Dausa districts. Since Desert is the end product of Desertification, identifying the problem at an early stage will be helpful. In this research paper, a straight line curve fit by Trend analysis method has been used to obtain an overall view of fluctuations in rainfall.